Lip repositioning technique. A simple surgical procedure to improve the harmony and symmetry of the smile: A case report - Dounia Sarfi; Sidi Mohammed Bouzoubaa; Ihsane Ben Yahya (Elsevier, 2022)
The excessive gingival display is an esthetic issue that is commonly managed by different procedures. Lip repositioning is a modality to address the concerns of affected patients. More than 3mm gingival display during smiling is considered as 'excessive gingival display' also known as "gummy smile", which is not attractive. The current case report presents a patient with a gummy smile managed by lip repositioning surgery. Our objective was to introduce lip repositioning as a successful treatment modality to decrease gingival show and manage its asymmetry using a simple and conservative surgical approach, with good durability in time, and with a minimum of recurrence.